Percepciones sobre la condición socioeconómica de migrantes venezolanos en Lima Metropolitana - Cáceres Torres, Carlos Eduardo (2022)
Venezuelan migration in Peru is estimated at close to one million people, where many of them have entered the labor market, encountering informality, poor working conditions, and discriminatory conditions. Given this, they have gone through adaptation and integration processes to survive and reorganize their livelihoods. This research exposes the perceptions of Venezuelan migrants regarding these lived processes and how from their experiences they have been building a new collective imaginary of a life project.